The natural history of the fallow deer, Dama dama (Linnaeus, 1758) in Bulgaria in prehistory and new evidence for the existence of an autochthonous Holocene population in the Balkans. (29th September 2020) - Karastoyanova, Nadezhda; Gorczyk, John; Spassov, Nikolai
Abstract: The fallow deer ( Dama dama Linnaeus, 1758 ) has a long history of interaction with prehistoric humans. Beginning in the Neolithic, humans introduced fallow deer to several areas of the eastern Mediterranean and mainland Europe, with later additional importing happening in the Bronze and Iron Ages. However, in some parts of southeastern Europe, autochthonous populations of extant fallow deer may have survived through the end of the Pleistocene and into the early Holocene, making them available for exploitation by Neolithic and Chalcolithic communities. Climatic and vegetational regimes favourable to fallow deer covered nearly all of Bulgaria during this period; yet, the heavy use of the species by human communities was restricted to a very small area around southeastern Bulgaria. Eventually, climate deterioration, habitat change and overhunting led to the decline of fallow deer in later prehistory in Bulgaria. This paper offers a discussion of the environmental and cultural background of human‐fallow deer interactions from the sixth to fourth millennium BCE in Bulgaria. Using bivariate scatterplots and log ratio techniques, we demonstrate that Neolithic and Chalcolithic communities exploited a large extant fallow‐deer population, appearing to target both males and females equally. Our results are the first step in a larger archaeological investigation of human‐fallow deer relations that unfolded over several millennia, touching upon issues of settlement, migration and perhaps even taming or domestication.